The importance of paratypical factors in the formation of productive longevity of red Gorbatov cows - O. V. Rudenko (Аграрная наука Евро-Северо-Востока, 2019)
The research was carried out on the basis of the breeding farm «Ababkovskoe» Nizhny Novgorod region. In the period of 2006-2015 518 heads of animals dropped out the herd. They formed the electronic database for studying the influence of paratypical factors on indicators of productive longevity of red Gorbatov cows. The analysis involving the method of grouping animals had been carried out. In the course of the study it was established that the increase in milk yield during the first lactation lead to an extension of productive life (r = 0.17). The best indicators (5.70 lactations) were observed in first-calf heifers having the yield of 5001-6000 kg of milk. Lifetime production and milk yield during the first lactation had a weak positive relation (r = 0.30). Cows with productivity of 5001-6000 kg of milk during the best lactation had the longest productive use (5.58 lactations). In general, there was an average positive relation between these indicators (r = 0.48). Power of influence of the highest lactation milk yield on the lifetime milk yield was 22.47% (F > Fst). In conditions of the red Gorbatov breed gene pool preservation the recommended milk yield for the first-calf heifers should be 4000-5000 kg of milk. The growth of milk production in subsequent lactations resulted in extension of the economic use of cows and increase in other productive indicators. Half of the animals in the herd (50.7%) had a coefficient of milk yield 751-1000 kg of milk per every 100 kg of live weight In this group there was the highest level of live weight (455 kg, р<0,001) and economic use (4.95 lactations, р<0,001). Great influence on the duration of red cow productive longevity had live weight during the first calving (power of influence 19.6% F > Fst).  The most optimal live weight for red Gorbatov cows during the first calving is not less than 460 kg. Low weight leads to a rapid drop out of animals from the herd